Influence of coupled effects between flexural tensile stress and carbonation time on the carbonation depth of concrete. (30th November 2018) - Wang, Jian; Su, Han; Du, Jinsheng
Highlights: The stress influence coefficient decreased with the increase of carbonation time. A model of stress influence coefficient considering the influence of carbonation time was proposed. The influence of the mix proportions of concrete on stress influence coefficient was studied. The effects of flexural tensile stress and carbonation time on carbonation depth were obviously coupled. A modified carbonation depth model of concrete was proposed. Abstract: Concrete stress has a great influence on the depth of carbonation, thus it is of vital importance to investigate the carbonation depth model under concrete stress state. Generally, the concrete structure has time-dependent characteristics, since as concrete ages, its strength, stiffness and other properties will also change. Therefore, under the same concrete stress and different carbonation time, the influence of concrete stress on carbonation depth will be different. To investigate the influence of the coupled effects between flexural tensile stress and carbonation time on the carbonation depth of concrete, a model of stress influence coefficient considering the influence of carbonation time was established by using the existing experimental data, and a modified carbonation depth model of concrete was proposed. Results indicated that the carbonation depth increased with an increase in flexural tensile stress level. As carbonation time increased under the same flexural tensile stress level, the stress influence coefficient decreased, and the computed results of the model of stress influence coefficient considering carbonation time were in good agreement with the experimental data. The maximum influence of the mix proportions of concrete on stress influence coefficient was limited, which was approximately within ±10%. The modified carbonation depth model was reasonable and had high prediction accuracy.